Students' Motivation in the Implementation of Madrasah Library to Enhance Literacy Culture in Fiqh Subject - Ridhawati Ridhawati; Jasmansyah Jasmansyah; Mustiali Mustiali; Muhammad Hori; Irfan Sofian; Harapandi Dahri; Early Adharini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to explore the role of the madrasah library in promoting literacy culture within the Fiqh subject. The primary objective was to identify the challenges faced by students in engaging with literacy and develop strategies to enhance their reading, writing, and discussion skills through library resources. Method: A qualitative descriptive approach was used, utilizing observation, interviews, and documentation as data collection methods. The data was analyzed thematically to identify key patterns related to literacy culture in Fiqh learning. Results: The findings indicate that students' low motivation to use the library significantly negatively impacted their literacy engagement. Several interventions were implemented to address this, including enhancing the library's physical environment, incorporating multimedia resources, offering incentives for active participation, and integrating literacy activities into Fiqh lessons. These interventions improved students' reading, writing, and discussion habits, encouraging critical thinking, creativity, and a deeper understanding of local wisdom. Novelty: This study introduces an innovative approach by embedding literacy culture within Islamic education through library-based initiatives targeted explicitly at Fiqh materials. Unlike previous research that viewed libraries as static information repositories, this study highlights their dynamic role in fostering literacy engagement. The findings contribute to the broader discourse on literacy development in religious education and emphasize the madrasah library as a key institution for sustaining a culture of enriched reading.